Precondition and possibilities for establishing cross border free zone between Mongolia-China (Journal of International Studies, 2018)
As for Mongolia, which is a landlocked and has vast land, establishment of free-trade and economic zone by extending border points with neighboring countries can be a main solution to keep border security, to promote regional development, to develop infrastructure of transportation and to expand trades. Recently, special focus on establishing cross-border free zone between Mongolia and China has been made and several negotiations in this field have been held by 2 countries’ governments. Therefore, the paper work aims to study pre-conditions and possibilities for establishing cross-border free zone between Mongolia and China. This thesis consists of following main 4 parts: 1) negotiations for cross-border free zone between Mongolia and China, 2) Cross-border free zone and Mongolian current situation, 3) Mongolia-China bilateral trade, 4) The possibility of establishing a cross-border free trade zone with China.